THE ESSENCE OF THE CONCEPTS OF «YOUTH» AND «POLITICAL PARTICIPATION OF YOUTH» (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines the concept of «youth» in political science from a conceptual perspective and explores its fundamental meaning in detail. It also examines various ways of defining the category of «youth» in Kyrgyz and international law, sociology, and political science. The significance of the youth strategy is considered in the context of various factors that distinguish this age and gender group. Various ways of developing youth policy are analyzed, taking into account the interests of stakeholders. The author also analyzes the concepts of «youth» and «youth political participation» in the context of political reforms and development goals in Kyrgyzstan. Based on the globalization trends of public life and the concept of age, the author opposes the idea of setting a lower age limit. The article analyzes the principles of developing a youth strategy based on an algorithmic approach and emphasizes that solving the objective problems of youth should be supplemented by integrating elements of youth policy into strategies, programs, and projects at all levels of government.
Keywords: youth, youth policy, political participation, public administration, socio-demographic group, etc.